Removal of COD from spent caustic wastewater of the Merox Unit - Bandar Abbas Oil Refinery using a combined Sono-electrocoagulation treatment system - Maryam Akbari; Mohammad Nasiri; Daryush Arabian; Roohollah Sadeghi (Desalination and Water Treatment)
Spent caustic wastewater, a byproduct of gas sweetening processes, is a challenging waste stream due to its alkaline nature, toxicity, corrosivity, and foul odor. This study investigated the effect of combining ultrasound with electrocoagulation to enhance chemical oxygen demand (COD) removal efficiency and minimize energy consumption in the treatment of spent caustic wastewater from the Bandar Abbas Oil Refinery (BAOR) in Iran. The performance of two hybrid ultrasonic systems—an ultrasonic bath (SEC-B) and an ultrasonic probe (SEC-P)—was compared under identical conditions. The results demonstrated that the ultrasonic bath (SEC-B) outperformed the ultrasonic probe (SEC-P). Subsequently, the effects of key process parameters, including treatment duration (T), electrode spacing (ES), and current density (CD), were optimized using the Box-Behnken Design (BBD). The optimal conditions were determined to be T = 24 minutes, ES = 2 cm, and CD = 17 mA/cm², which led to a COD removal efficiency of 80 % and energy consumption of 3.78 kWh/m³ . The addition of ultrasound to the electrocoagulation process, slowed the development of a passive layer on the electrode surface, reduced its thickness, and enhanced the generation of hydroxyl radicals. This synergistic effect enhanced COD removal efficiency by about 28 % and reduced energy consumption by about 42 %. These findings demonstrate the potential of SEC as an efficient technique for treating spent caustic wastewater. Finally, suggestions for enhancing process efficiency in future studies are provided.